Izbrana poglavja iz fiziologije za študente medicine z navodili za vaje - Stožer, Andraž; Križančić Bombek , Lidija; Dolenšek, Jurij; Skelin Klemen, Maša (University of Maribor Press, 2021)
Selected Chapters in Physiology for Medical Students with Instructions for Practicals. The textbook Selected Chapters in Physiology for Medical Students with Instructions for Practicals guides a student through physiology of excitable cells during the first two chapters. In the following chapters general physiology of selected organs of the human body is discussed. Several chapters are dedicated to cardiovascular physiology, instructing students to learn about the concepts of arterial pressure, methods to measure electrical activity of the heart using electrocardiogram, and parameters that change the cardiac output. The last three chapters imply some organs in the context of the whole body, teaching a student the inter-organ interactions and reaction of the body to external stressors. Each chapter addresses pathological states that are relevant for the respective subject and subsequent deepening of the understanding how human body functions. Moreover, they present an introduction to the clinical courses during medical study. Theoretical introduction of a chapter is followed by detailed instructions for the practicals that guide a student to either independently or with a help a fellow colleague through measurements and analysis of physiological parameters of the human body. 2nd reprint of first edition: 23. 5. 2022 3rd reprint of first edition: 24. 6. 2024 4th reprint of first edition: 27. 5. 2026